Human Bocavirus: A Cause of Severe Asthma Exacerbation in Children - Vallet, Christelle; Pons-Catalano, Charlotte; Mandelcwajg, Alexis; Wang, Andrew; Raymond, Josette; Lebon, Pierre; Gendrel, Dominique (The Journal of pediatrics, 2009)
Real-time polymerase chain reaction for human bocavirus (HBoV) was performed in nasopharyngeal aspirate specimens from 166 children over 2 years of age hospitalized for severe asthma exacerbation. Whereas HBoV was detected in 21 of these children (13%), it was found in only 1 of 50 ambulatory children with stable asthma (2%), suggesting a major role of HBoV in acute exacerbations in asthmatic children.